Correlation of cone resistance with undrained shear strength for clay soil [electronic resource] - Ismail Abd. Rahman 260781 (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2007